2013
DOI: 10.1148/radiol.13122149
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric Prostate MR Imaging with T2-weighted, Diffusion-weighted, and Dynamic Contrast-enhanced Sequences: Are All Pulse Sequences Necessary to Detect Locally Recurrent Prostate Cancer after Radiation Therapy?

Abstract: MP MR imaging has greater accuracy in the detection of recurrent PCa after RT than T2-weighted imaging alone, with no additional benefit if DCE is added to T2-weighted imaging and DW imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
76
2
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(86 citation statements)
references
References 37 publications
4
76
2
4
Order By: Relevance
“…These results are comparable with our study, where sensitivity ranged between 0.85 and 0.97 with and 0.76 and 0.82 without the usage of an ERC, and demonstrate that images acquired without an ERC may be sufficient for the purpose of detection of prostate cancer. Inter- and intra-reader agreement in our study was within the range of previously published results [34,35,36,37] and did not differ between the two coil setups investigated.…”
Section: Discussionsupporting
confidence: 90%
“…These results are comparable with our study, where sensitivity ranged between 0.85 and 0.97 with and 0.76 and 0.82 without the usage of an ERC, and demonstrate that images acquired without an ERC may be sufficient for the purpose of detection of prostate cancer. Inter- and intra-reader agreement in our study was within the range of previously published results [34,35,36,37] and did not differ between the two coil setups investigated.…”
Section: Discussionsupporting
confidence: 90%
“…In the subgroup of patients lower-grade PCa, the summed PI-RADS score of T2WI and DWI only resulted in similar good test accuracy. In agreement with mp-MRI after radiation therapy, there were no additional benefits if DCE was added to T2WI and DWI [20]. However, for higher-grade PCa detection, DCE further improved data accuracy.…”
Section: Discussionmentioning
confidence: 54%
“…In another study, Morgan et al [36] also emphasized the added vale of DWI, concluding that ADC measurement is useful for detecting local tumor relapse larger than 0.4 cm 2 within the prostate. In a more recent study, Donati et al [37] concluded that the combination of T2WI and DWI achieves the best overall diagnostic accuracy and the highest inter-reader agreement in the detection of recurrent PCa after RT. In other studies, Arumainayagam et al [38] and Akin et al [39] demonstrated that mp-MRI using T2WI, DCE-MRI, and DWI is an accurate test for detecting radio-recurrent PCa.…”
Section: External Beam Radiotherapymentioning
confidence: 99%